THE EFFECT OF INTERACTIVE DIGITAL SIMULATION ON THE QUALITY OF PHYSICS PRACTICUM LEARNING: A STUDY OF INNOVATION IN INDUSTRIAL ENGINEERING EDUCATION IN THE DIGITAL ERA - Nugraha, Billy; Zukhruf, Friska Putri; Setiawan, Handika; Amin, Moh. Rizha Fauzi; Kharisma, Nadhira Septias (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2024)
This study aims to evaluate the influence of the use of interactive digital simulations in improving the quality of physics practicum learning in S1 Industrial Engineering students in the digital era. The research method used is quantitative with a survey design. Data was collected from 163 Industrial Engineering student respondents through a questionnaire that measured various aspects of learning, including material comprehension, student engagement, satisfaction, and the effectiveness of material delivery by practicum assistants. Statistical analysis was carried out using descriptive analysis and linear regression to determine the relationship between the use of digital simulations and these learning variables. The results show that the use of interactive digital simulations significantly improves the quality of physics practicum learning. Students reported significant improvements in understanding of physics concepts, increased engagement during practicums, and higher satisfaction with these new learning methods. The effectiveness of material delivery by practicum assistants has also increased, in accordance with the clarity and timeliness of material delivery through digital platforms. In conclusion, the application of interactive digital simulations in physics practicum has a significant positive impact on the quality of learning among Industrial Engineering students. This study suggests expanding the use of digital technology in other academic activities to maximize learning outcomes and student engagement in the ever-evolving era of digitalization.